2006
DOI: 10.1021/ic061377u
|View full text |Cite
|
Sign up to set email alerts
|

Expanding the Scope of Sulfur-Centered Arbuzov Rearrangement in Diethyl/Di-n-propyl Sulfite for the Synthesis of Mixed-Ligand Di-n-butyltin Alkanesulfonates

Abstract: A one-pot reaction between di-n-butyltin oxide and diethyl/di-n-propyl sulfite in the presence of an equimolar amount of alkyl iodide proceeds via sulfur-centered Arbuzov rearrangement to afford the corresponding di-n-butyltin (alkoxy)alkanesulfonates n-Bu2Sn(OR')OS(O)2R [R = R' = Et (1), n-Pr (2); R = Me, R' = Et (3), n-Pr (4)]. The compounds 1 and 3 react with methylphosphonic acid under mild conditions to give [n-Bu2Sn(OS(O)2R)OP(O)(OH)Me]n [R = Et (5), Me (6), respectively].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 22 publications
2
10
0
Order By: Relevance
“…In a recent communication, we have also reported the utility of diethyl/di-n-propylsulfite as a synthon to afford the corresponding di-n-butyltin(alkoxy)alkanesulfonates (Eq. (1)) [7].…”
Section: Introductionmentioning
confidence: 99%
“…In a recent communication, we have also reported the utility of diethyl/di-n-propylsulfite as a synthon to afford the corresponding di-n-butyltin(alkoxy)alkanesulfonates (Eq. (1)) [7].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the anion containing atom S3 only acts as a monodentate ligand. Some -O:O 0 -bridging ethanesulfonate ligands are also found in dinuclear chloride-sulfonate-antimony(V) complexes (Burchardt et al, 1998;Lang et al, 1998) and in polymeric chains of the dioxouranium(VI) complex [(UO 2 )(H 2 O)(C 2 H 5 SO 3 ) 2 ] (Alcock et al, 1993) and the ethanesulfonate-hydrogenmethanephosphonate-diorganyltin(IV) compound [(C 4 H 9 ) 2 -Sn{OP(O)(OH)CH 3 }OS(O) 2 C 2 H 5 ] (Shankar et al, 2006). In contrast to this bridging mode, the ethanesulfonate group in the polymeric chain structure of [Cu(CO)C 2 H 5 SO 3 ] is 1O:2O 0 ,O 00 -bridging (Doyle et al, 1983).…”
Section: Commentmentioning
confidence: 99%
“…We have reported a new family of layered mixed-ligand diorganotin (IV) 2 , which incorporate ring, ladder, and trinuclear tin cluster entities in their structural frameworks. [12] In a recent report, we demonstrated that the incorporation of silaalkylphosphonate ligands into diorganotin(IV) coordination polymers endows enhanced solubility in common organic solvents. This intrinsic property has been utilized to transform the bulk samples into colloidal dispersions featuring rod, rosette, and spherical morphologies.…”
Section: Introductionmentioning
confidence: 98%